Devil's due eaudiobook - Anderson, Taylor (Destroyermen, 2017)
Taylor Anderson continues his powerful New York Times bestselling series of alternate history and military strategy, as the conflict is about to become terrifyingly personal . . . Captain Matt Reddy and the crew of the USS Walker have been fighting for their lives ever since their ship was swept from the Pacific to another world and they became embroiled in a deadly conflict between their Lemurian allies and the ravening Grik. But things are about to get worse. With Reddy's family and allies held prisoner by the mad General Kurokawa, the mysterious League and evil Dominion plotting schemes of their own, and the Grik trying to build their swarm and concentrate power, Reddy faces danger on all sides. Although desperate to confront Kurokawa, Captain Reddy fears he's subordinating the war effort for personal reasons. But Kurokawa is too dangerous to be left alone. With the mighty League battleship Savoie at his command, he plots a terrible vengeance against Reddy and his tiny, battered destroyer. The stage is set for a devastating cataclysm, and Reddy and his allies will have to risk everything to protect what they hold dear.